2021
DOI: 10.1097/mol.0000000000000770
|View full text |Cite
|
Sign up to set email alerts
|

Lipids and peripheral neuropathy

Abstract: Purpose of review Hyperlipidaemia is associated with the development of neuropathy. Indeed, a mechanistic link between altered lipid metabolism and peripheral nerve dysfunction has been demonstrated in a number of experimental and clinical studies. Furthermore, post hoc analyses of clinical trials of cholesterol and triglyceride-lowering pharmacotherapy have shown reduced rates of progression of diabetic neuropathy. Given, there are currently no FDA approved disease-modifying therapies for diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 111 publications
1
24
0
Order By: Relevance
“…Other treatments for improving wound closure in patients with diabetes and neuropathy include antibiotics if an infection is present, as well as debridement and wound cleansing [ 25 ]. Recent evidence also suggests that hyperlipidemia, specifically hypertriglyceridemia, may play a role in the development of diabetic neuropathy and therefore, lipid-lowering drugs may prevent or even reverse the damage to nerve fibers in patients with diabetic neuropathy [ 26 ]. This approach to prevention is not often employed as therapies targeting neuropathy currently focus on reducing the pressure placed on the foot and relieving the need to itch [ 25 ].…”
Section: Pathophysiology Associated With Diabetic Wound Healingmentioning
confidence: 99%
“…Other treatments for improving wound closure in patients with diabetes and neuropathy include antibiotics if an infection is present, as well as debridement and wound cleansing [ 25 ]. Recent evidence also suggests that hyperlipidemia, specifically hypertriglyceridemia, may play a role in the development of diabetic neuropathy and therefore, lipid-lowering drugs may prevent or even reverse the damage to nerve fibers in patients with diabetic neuropathy [ 26 ]. This approach to prevention is not often employed as therapies targeting neuropathy currently focus on reducing the pressure placed on the foot and relieving the need to itch [ 25 ].…”
Section: Pathophysiology Associated With Diabetic Wound Healingmentioning
confidence: 99%
“…Interestingly, quite coinciding findings were revealed by Zhao et al, who concluded that following treatment with fenofibrate, there was a significant reduction in triglyceride levels and a marked increase in total HDL [ 16 ]. The Study for Atrial Fibrillation Reduction (SAFARI) trial also observed these findings, which saw a 23.6% reduction in triglyceride levels and an 8.8% increase in HDL following combined use of statin and fenofibrate [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 98%
“…Most studies discovered that the prevalence of diabetic microvascular complications increased with age and duration ( 13 ). Hypertension and lipid metabolism disorders has a promoting effect on the development of microvascular lesion in diabetes ( 14 , 15 ). Another widely recognized factor is HbA1c, which can be used as an important indicator for blood glucose levels and diabetic microvascular complications ( 16 ).…”
Section: Discussionmentioning
confidence: 99%